Resistivity piezocone for geo-environmental site characterization: Two case histories from Brazil - Giacheti, Heraldo Luiz [UNESP]; Peixoto, Anna Silvia Palcheco [UNESP]; Mondelli, Giulliana; De Mio, Giuliano (My University, 2006)
This paper presents two case histories from Brazil where geophysical and resistivity piezocone tests were carried out to detect contamination. At the first one, the site investigation program was carried out to detect salt-water intrusions in a superficial sedimentary aquifer, at the Paranaguá harbor, in Paraná State. The second case history is a sanitary landfill from Bauru City, São Paulo State. In both sites, superficial geophysical tests were interpreted to detect and delineate the shape of contamination plume, helping to locate the resistivity piezocone tests. It was found that the interpretation of resistivity piezocone tests is straightforward to assess salt-water intrusion in sedimentary sands. For tropical soils, this technique presented some limitations since the groundwater table sometimes is deeper than the layer penetratable to the cone. Moreover, the genesis of those soils affects soil behavior and soil and water sampling is required to support interpretation.
Keywords: Aquifers; Characterization; Contamination; Sand; Sediments; Water; Geophysical tests; Piezocone; Sedimentary sands; Geophysics